Effect of Professional Ethics and Emotional Intelligence on Auditor Performance - Shofia Asry; Helmina Ginting (Kusuma Negara Business School, 2020)
The development of the company is currently affecting the profession of public accounting. The more a company develops, the more the public accounting profession will develop. Public accountant is an independent party whose duty is to examine and assess whether the financial statements have been presented fairly and in accordance with generally accepted accounting principles. Many phenomena indicate that the auditor's performance in the examination or assessment process for interested parties is still far from good. The auditor must carry out ethical standards and support the goals of professional norms which are one aspect of professional commitment. Auditor performance is not only seen from the ability to work perfectly, but also the ability to master and manage themselves and the ability to foster relationships with others (Emotional Intelligence / emotional intelligence). The results in this study indicate that emotional intelligence and professional ethics together (simultaneously) significantly influence the performance of auditors at the Public Accountant Office in Pasar Minggu sub-district, South Jakarta. These results can be seen the calculated F value of 41,644 with a significant level of 0,000. Because the significant probability is much smaller 5% (0.05) obtained from the results of the regression analysis and the terminated coefficient (R2) or adjusted R Square of 0.687 or 68.7% auditor performance variables that can be explained by variables of professional ethics and emotional intelligence, while the remaining 31.3% is explained by other variables not included in this study.